MORTALIDAD Y DESENLACES CLÍNICOS EN PACIENTES CRÍTICAMENTE ENFERMOS CON INFECCIONES POR BACTERIAS PRODUCTORAS DE CARBAPENEMASAS EN UN HOSPITAL DE ALTA COMPLEJIDAD EN BOGOTÁ, COLOMBIA - Fabio Andres Varón (Asociación Colombiana de Infectología, 2021)
Introduction: Microorganisms able to produce carbapenemases are spreading worldwide and have become a concerning global public-health problem. In Colombia, the Gram-negative resistance to carbapenems at intensive care units is currently increasing and its impact on clinical outcomes is not well known. Objectives: To determine the demographic, clinical characteristics and outcomes of critically ill adult patients with infection by carbapenemase producing bacteria in a polyvalent intensive care unit of a highly complex institution. Methods: Single-center retrospective, descriptive observational study including critically ill adult patients infected by carbapenemase-producing bacteria and transferred to a polyvalent intensive care unit from January 1th 2014 to January 1th 2018. Known colonized patients were excluded. Clinical complications, ICU and in-hospital days of stay were evaluated, as ICU and in-hospital mortality. Results: A total of 58 patients were included. Overall mortality was 67.2%, of which 55.17% died during their stay in the intensive care unit and 12.06% in hospitalization. The median stay in the intensive care unit was 18 days (IQR 4-28). The most frequent cause of death was septic shock in 51% and the most common complications were acute renal injury and delirium in 55.2% and 43.1%, respectively. The median stay in the ICU was 18 days (RIQ 4-28). Conclusions: Infections caused by carbapenem-resistant bacteria in critically ill patients are associated with high mortality rates, complications and long stay in ICU.